2011
DOI: 10.1007/s10641-010-9764-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification of Thunnus orientalis, T. thynnus, and T. maccoyii by a cytochrome b gene analysis

Abstract: The three species of bluefin tunas, Thunnus orientalis, T. maccoyii, and T. thynnus, are morphologically similar, which can pose problems for fisheries management and marketing. We examined intraspecific genetic diversity and interspecific genetic boundaries among these three species by analyzing the cytochrome (Cyt) b gene. The full lengths of the nucleotide sequences were 1,141 bp in T. orientalis and T. thynnus and ranged 1,138~1,141 bp in T. maccoyii. Mean nucleotide diversities were 0.0019± 0.0002 in T. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The use of mitochondrial Cyt-b gene to perform the analysis of genetic diversity and population genetic structure studies had been done in many closely related fishes (Norfatimah et al, 2009;Pereyra et al, 2010;Tseng et al, 2011). The gene also holds viable information regarding the phylogenetic relationships within and between the individuals of the same population.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mitochondrial Cyt-b gene to perform the analysis of genetic diversity and population genetic structure studies had been done in many closely related fishes (Norfatimah et al, 2009;Pereyra et al, 2010;Tseng et al, 2011). The gene also holds viable information regarding the phylogenetic relationships within and between the individuals of the same population.…”
Section: Discussionmentioning
confidence: 99%
“…Two sets of primers and amplification conditions were used to amplify the complete Cyt b gene and control region of mtDNA (Tseng et al, 2009(Tseng et al, , 2011. Amplification was performed in a BIO-RAD MJ Mini Gradient Thermal Cycler (Conmall Biotechnology, Singapore).…”
Section: Dna Isolation and Polymerase Chain Reaction (Pcr) Amplificationmentioning
confidence: 99%
“…These features of mtDNA are used by evolutionary biologists to establish relationships and to trace maternal lineage of species using array of sequence data. The displacement loop (D-loop) is the most variable region of mtDNA [19] and previous research reported that high variation in the region is useful in characterizing tilapia species [20] [27]. In the present study, it was our aim to assess the phylogenetics of Oreochromis niloticus, a common species of tilapia fish in Nigeria using mitochondrial D-loop and Cytb.…”
Section: Introductionmentioning
confidence: 99%